2020
DOI: 10.1051/0004-6361/202038397
|View full text |Cite
|
Sign up to set email alerts
|

Superflares on the late-type giant KIC 2852961

Abstract: Context. The most powerful superflares reaching 1039 erg bolometric energy are from giant stars. The mechanism behind flaring is thought to be the magnetic reconnection, which is closely related to magnetic activity (including starspots). However, it is poorly understood how the underlying magnetic dynamo works and how the flare activity is related to the stellar properties that eventually control the dynamo action. Aims. We analyze the flaring activity of KIC 2852961, a late-type giant star, in order to under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…According to Figure 9(b), the flaring lengths of superflares on KIC 2852961 are less than the diameter of this star (R star = 2R * ). These results also strengthen the conclusion from Kővári et al (2020) that the largest flares of KIC 2852961 have flare loop sizes on the order of R * .…”
Section: Superflare Energy and Durationsupporting
confidence: 85%
See 1 more Smart Citation
“…According to Figure 9(b), the flaring lengths of superflares on KIC 2852961 are less than the diameter of this star (R star = 2R * ). These results also strengthen the conclusion from Kővári et al (2020) that the largest flares of KIC 2852961 have flare loop sizes on the order of R * .…”
Section: Superflare Energy and Durationsupporting
confidence: 85%
“…Recently, statistical research on superflares on giant stars has been done by Kővári et al (2020). They used Kepler and a small part of the TESS data and searched 60 superflares on the star KIC 2852961.…”
Section: Superflare Energy and Durationmentioning
confidence: 99%
“…Other studies have used the measured flare recovery rate to correct the observed flare frequency distribution, to which a power law is then fit (e.g. Ilin et al 2019;Kővári et al 2020). This has the benefit of keeping lower energy flares in the fitted distribution while still accounting for the detection efficiency.…”
Section: Fitting the Average Flare Occurrence Ratementioning
confidence: 99%
“…4.3 range over four magnitudes. Recently, Kővári et al (2020) have concluded that, in principle, differences between flare energies are due to size effect, regardless of energy range or spectral type (cf. Balona 2015).…”
Section: Flare Statisticsmentioning
confidence: 99%